PELATIHAN E-COMMERCE BERBASIS WEB UNTUK MENUMBUHKAN POTENSI SISWA SMK BERWIRAUSAHA - Rizki Noor Prasetyono; Rito Cipta Sigitta Hariyono (Universitas Amikom Purwokerto, 2019)
Computerized and information technology technology is now developing rapidly throughout society. The impact of this technology also affects the system in the community which is the simplest system of buying and selling. E-commerce that affects changes in the buying and selling process, where buying and selling transactions are not always done face-to-face. Objectives To foster entrepreneurial skills in SMK Karya Bakti Brebes students through Web-based E-Commerce training. Entrepreneurship is a skill that can be developed and beneficial for vocational students to do business in various fields in generating independent profit. Through the method of carrying out activities through the preparation stage, namely planning to make teaching materials for training and observation in the potential of students' interest in the field of entrepreneurship. The activity phase carries out the process of granting competency in making and Web-based E-Commerce Innovation. This evaluation phase knows the level of success so that a follow-up process can be carried out. The dedication carried out at the Vocational School Bhakti Brebes received a good reception from the school both from the principal, teachers, and all staff working there. Activities develop entrepreneurial skills from students so that when they graduate students get provisions in working or creating job opportunities, or entrepreneurship